Upaya Pemerintah Dalam Penanggulangan Tindak Pidana Peredaran Kosmetika Palsu - Meni Apriani; Yuseva Yuseva; Dedison Dedison; Heli Kusmiran; M. Agung Firdaus (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Counterfeiting cosmetics is not just brand counterfeiting but is also an act that endangers human life if the contents of the cosmetics are inappropriate or unclear. What is the government's responsibility towards the circulation and use of illegal cosmetics? What legal remedies can the community take against the distribution of illegal cosmetic products? The research method uses an empirical juridical method because this research aims to describe in full the legal aspects and a situation that occurs in the field. The results of the study show that the Government's responsibility in terms of the circulation and use of illegal cosmetics in Palembang City is to supervise and guide all business actors. Efforts made by the community against the distribution of illegal cosmetics are for consumers who feel disadvantaged by business actors, they can make several efforts to resolve their disputes through the courts and through the Consumer Dispute Settlement Agency (BPSK). In conclusion, it is the responsibility of the government in terms of the distribution and use of illegal cosmetics with supervision and legal remedies through the courts. Recommendations It is hoped that business actors should also be able to provide information to consumers regarding cosmetic products that are sold in a clear and open manner, consumers should also be more careful before buying a product and not immediately trust cosmetics that are sold at low prices.